Microbiological quality of microgreen seeds purchased from online vendors and evaluating seed decontamination techniques available online - Ocho Bernal, Thalia Guadalupe; Lyttle, Nathan; Jung, Yangjin (Frontiers in Sustainable Food Systems, 2023)
This study aimed to assess the microbiological quality of microgreen seeds purchased online, including the levels of total aerobic plate counts (APC), Escherichia coli/coliforms, mold & yeast, and the presence of Salmonella spp. and Listeria monocytogenes. Additionally, seed decontamination practices commonly found online were evaluated, involving soaking in water only (SDW), 3% hydrogen peroxide (H), and a "poor man's solution" (HV; a mixture of 3% hydrogen peroxide and 5% acidity white vinegar with water), with or without heat treatment at 50 °C and 60 °C for 20 and 40 h. The effectiveness of these treatments was evaluated using Amaranth (AM), Borage (BO), and Carrot (CA) seeds in reducing Enterobacteriaceae, coliforms, and mold & yeast, along with examining the germination rate. A total of 102 samples composed of 14 species were purchased from online vendors, and the microbial levels tested were significantly different among the seed species (p<0.05). Among the species, BO, CA, and Onion (ON) seeds exhibited the highest APC levels (4.99 -5.37 log CFU/g), which was significantly higher than the APC of Arugula, Cabbage, Mustard, Kale, and Pea seeds (p < 0.05). The coliform population of BO (3.77 ± 0.68 log CFU/g) was significantly higher than in other species. The 10-min soaking of AM, BO, and CA in H significantly reduced the microbial levels (p < 0.05), and the subsequent heat treatment at 60 °C for 20 h further enhanced microbial reduction (total 1.2-3.4 log reduction by heat and soaking). The germination rates were not significantly affected by the different treatment combinations (p > 0.05). This study provides scientifically-validated data for small-scale and home growers to ensure the safety and improve the quality of microgreens.